2020
DOI: 10.1002/jso.26277
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathologic examination of myxofibrosarcoma. Do surgical margins significantly affect local recurrence rates in this infiltrative sarcoma subtype?

Abstract: Background and ObjectivesMyxofibrosarcoma (MFS) is an aggressive soft tissue tumor with an unpredictable recurrence pattern. We sought to (a) determine whether margin status in MFS is correlated to rates of local recurrence (LR) and (b) identify demographic and treatment variables associated with disease‐related outcomes in this population.MethodsThis retrospective study identified 42 surgically treated patients with MFS over 10 years at a single institution. Patient demographics, tumor characteristics, intrao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…The histological diagnosis of myxo brosarcoma was the only factor that in uenced LRFS. Myxo brosarcoma has a locally in ltrative behavior and is associated with a high local recurrence rate of 24-44% [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histological diagnosis of myxo brosarcoma was the only factor that in uenced LRFS. Myxo brosarcoma has a locally in ltrative behavior and is associated with a high local recurrence rate of 24-44% [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Muramatsu et al reported four cases with defects of the exor or extensor forearm muscle after tumor resection that received functional neurovascular musculocutaneous aps (free re-innervated transfer of gracilis or LD) to reconstruct nger exors and extensors 9 . Reinnervation of the transferred muscle was obtained in all cases, and functional outcomes were evaluated as good to excellent, with a median MSTS score of 28 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). We usually reconstruct exors, extensors, or both muscle groups ( exor digitorum profundus [FDP], extensor digitorum [ED], exor pollicis longus [FPL], and extensor pollicis longus [EPL]) using tendon autografts or tendon transfer techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Dadrass et al [ 71 ] in a homogeneous series of MFS, found an association of LR with positive margin resection. Interestingly, the rate of LR in negative margin resections was relatively high compared to other STS subtypes.…”
Section: Margins In Specific Sts Histotypesmentioning
confidence: 99%
“…This highlights that specific infiltrative STS can highly recur even if excised with wide margins. Although negative margins may be achieved during resection, the irregular histologic pattern of MFS can still reveal microscopically positive margins on histopathology, more often than would be expected in other histotypes [ 71 ]. Fujiwara et al [ 72 ] demonstrated that in the case of MFS and UPS, neither the R-classification nor the R1-classification were able to stratify the risk of LR in patients with negative margins, indicating that these classification systems are not sufficiently sensitive to stratify what constitutes an adequate margin of resection for infiltrative STS.…”
Section: Margins In Specific Sts Histotypesmentioning
confidence: 99%
“…CI, confidence interval [Color figure can be viewed at wileyonlinelibrary.com] "How much margin is optimum" is another question that is still often debated in the surgical management of STS as they are a heterogeneous group of tumors comprising of more than 50 histological subtypes having varying tumor biology and aggressiveness. 7,8 Different widths of negative margins (clear <1, 1-5, 5-10, >10 mm) have been correlated with survival in various studies, extra wide margins (>10 mm) have not been shown to improve loco-regional disease control. 9,10 All attempts must be made to achieve microscopically negative margins in all dimensions following resection of an STS in a nonmetastatic curative setting for optimal treatment outcomes.…”
mentioning
confidence: 99%